Towards a comprehensive understanding of distortion in additive manufacturing based on assumption of constraining force. (8th September 2021) - Xie, Deqiao; Lv, Fei; Liang, Huixin; Shen, Lida; Tian, Zongjun; Zhao, Jianfeng; Song, Yingdong; Shuai, Cijun
ABSTRACT: Additive manufacturing has shown giant potential in advanced manufacturing industry. However, distortion of additive-manufactured parts may interrupt the printing process and decrease manufacturing precision, causing a significant waste of time and money. Distortion, a common problem in additive manufacturing, has not been sufficiently researched. In this study, we provide a comprehensive understanding of distortion in additive manufacturing based on assumption of constraining force. A quantitative model was established to illustrate inconsistent shrinkage during the additive process. A qualitative model was then built for showing the distortion caused by inconsistent shrinkage. It can be founded that inconsistent shrinkage accumulated during the additive process drives the final distortion of part. We concluded most influencing factors of distortion together, forming towards a comprehensive understanding of distortion in additive manufacturing. This study not only links micro melting-solidification process and macro structural mechanics in science, but also provides systematic solutions for decreasing the distortion in additive manufacturing for engineering.